2017
DOI: 10.1111/ijac.12831
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of calcium aluminate cement by combustion synthesis and application for corundum‐based castables

Abstract: Calcium aluminate cement was prepared by combustion synthesis with CaO2, Al, and Al2O3 as raw materials. The effects of CaO/Al2O3 (C/A) molar ratios in raw materials on the phase compositions and morphologies of calcium aluminate were investigated in detail. It was found that when the C/A reduced from 1.1 to 0.74, the content of CaO·2Al2O3 (CA2) in products increased, whereas contents of CaO·Al2O3 (CA) and 12CaO·7Al2O3 (C12A7) decreased; when the C/A was 0.8, the phase composition of product (CS71) was equal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As raw materials, calcium peroxide powder (CaO 2 , particle size <25 µm), calcium carbonate powder (CaCO 3 , particle size <25 µm), aluminum powder (Al, particle size 2~3 µm) and alumina powder (Al 2 O 3 , particle size <74 µm) of analytical purity were purchased from Sinopharm Chemical Reagent (Shanghai) Co. Ltd. A previous study reported that the phase compositions of the combusted product were equal to those of commercial Secar71 when the molar ratio of CaO/Al 2 O 3 (C/A) in the ratio of raw materials CaO 2 , Al and Al 2 O 3 was 0.8 [30]. Therefore, aiming at the combustion synthesis of in-situ nanocarbon/aluminate composites with similar phase compositions to commercial Secar71, the C/A molar ratio was fixed at 0.8 in the present study, and CaCO 3 was used as a carbon and calcium source to partially replace CaO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As raw materials, calcium peroxide powder (CaO 2 , particle size <25 µm), calcium carbonate powder (CaCO 3 , particle size <25 µm), aluminum powder (Al, particle size 2~3 µm) and alumina powder (Al 2 O 3 , particle size <74 µm) of analytical purity were purchased from Sinopharm Chemical Reagent (Shanghai) Co. Ltd. A previous study reported that the phase compositions of the combusted product were equal to those of commercial Secar71 when the molar ratio of CaO/Al 2 O 3 (C/A) in the ratio of raw materials CaO 2 , Al and Al 2 O 3 was 0.8 [30]. Therefore, aiming at the combustion synthesis of in-situ nanocarbon/aluminate composites with similar phase compositions to commercial Secar71, the C/A molar ratio was fixed at 0.8 in the present study, and CaCO 3 was used as a carbon and calcium source to partially replace CaO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the CVD process, which consumes flammable and explosive gases directly, CO 2 gas that originates from the decomposition of carbonate during the process of combustion synthesis acts as a carbon source for the formation of in-situ nanocarbons. The combustion method has been applied to the synthesis of aluminate cement [26][27][28][29][30][31] and nanocarbon materials [32,33]. Therefore, the synthesis of in-situ nanocarbon/aluminate composites via the combustion method is feasible.…”
Section: Introductionmentioning
confidence: 99%